“Procedural sedation and analgesia in Italian pediatric emergency departments: a subgroup analysis in italian hospitals" - Martina Bevacqua; Idanna Sforzi; Silvia Bressan; Egidio Barbi; Cyril Sahyoun (Italian Journal of Pediatrics, 2023)
Abstract To date, pain and anxiety are the most common symptoms reported by children who refer to pediatric emergency department. Despite it is well known that the undertreatment of this condition has some negative consequences in a short term and long term of time, gaps in the management of pain in this setting still persist. This subgroup analysis aims to describe the current state of art of pediatric sedation and analgesia in Italian emergency departments and to identify existing gaps to solve. This is a subgroup analysis of a cross-sectional European survey of pediatric emergency departments sedation and analgesia practice undertaken between November 2019 and March 2020. The survey proposed a case vignette and questions addressing several domains, like the management of pain, availability of medications, protocols and safety aspects, staff training and availability of human resources around procedural sedation and analgesia. Italian sites responding to the survey were identified and their data were isolated and checked for completeness. Eighteen Italian sites participated to the study, the 66% of which was represented University Hospitals and/or Tertiary Care Centers. The most concerning results were an inadequate sedation to 27% of patients, lack of availability of certain medications like nitrous oxide, the lack of use of intranasal fentanyl and topical anesthetics at the triage, the rare use of safety protocols and preprocedural checklists, lack of staff training and lack of space. Furthermore, the unavailability of Child Life Specialists and hypnosis emerged. Despite procedural sedation and analgesia in Italian pediatric emergency departments is progressively more used than previously, several aspects still require an implementation. Our subgroup analysis could be a starter point for further studies and to improve and make the current Italian recommendations more homogeneous.